From redox chemistry to biological uptake: Mechanistic controls on the environmental behavior of essential and toxic trace elements - Rehman, Hamid; Gul, Nida; Rehman, Ziafat; Iqbal, Mazhar; Naeem, Rehan; Debik, Eyup (ELSEVIER, 2026)
Background: Redox-sensitive trace elements such as iron (Fe), manganese (Mn), selenium (Se), and chromium (Cr) exhibit multiple oxidation states that strongly control their environmental mobility, bioavailability, and toxicity. Variations in redox conditions across natural and engineered systems drive dynamic transformations that regulate element cycling and exposure pathways. Objectives: This review aims to provide a mechanistic synthesis of how redox transformations govern speciation, transport, and biological uptake of Fe, Mn, Se, and Cr across environmental compartments, while linking analytical constraints with environmental risk assessment. Key findings: Under reducing conditions, dissolved Fe(II) and Mn(II) can reach 0.1-100 mg L-& sup1;, whereas oxidized Fe(III) and Mn(IV) form low-solubility oxides with high sorption capacity. Selenium oxyanions typically occur at <0.1-100 & micro;g L-& sup1; but may exceed 1000 & micro;g L-& sup1; in contaminated systems, while Cr(VI) remains highly mobile and toxic compared to relatively immobile Cr(III). Microbial reduction, organic complexation, and colloidal transport can enhance trace element mobility by approximately 20-80%. Conclusions: Trace element behavior is governed primarily by chemical speciation rather than total concentration, emphasizing the need for redox-based mechanistic frameworks in environmental assessment. Future research should integrate high-resolution analytical techniques with predictive modeling to better capture redox dynamics, reduce uncertainty in speciation measurements, and improve risk assessment in complex environmental systems.
Keywords: Redox speciation; Elements cycling; Colloidal transport; Uptake processes; Reactive species; DISSOLVED MN(III); SELENIUM; SPECIATION; REDUCTION; OXIDATION; SEDIMENTS; REMOVAL; CARBON; GROUNDWATER; IRON(II); Environmental Sciences & Ecology